Effects of observing employees for food safety compliance rates. - York, Valerie K.; Brannon, Laura A.; Roberts, Kevin R.; Shanklin, Carol W.; Howells, Amber D.; Barrett, Elizabeth B. (My University, 2014)
Research investigating foodservice employees’ compliance with food safety guidelines often utilizes observational methodology where an observer is present and recording employees’ behaviors as they work. Research must determine if the observer’s presence influences employees who are trained in food safety and those who are not. A group who had received a four‐hour ServSafe® food safety training course and a control group were included in the study (N=252). Both groups’ compliance rates were higher during the first hour of the observation compared to the last two hours of the observation. Implications for foodservice managers, researchers, and health inspectors are discussed.
Keywords: Food safety; Restaurant employees; ServSafe® training; Observation methodology; Social desirability; Habituation